2017
DOI: 10.3892/ol.2017.7562
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-196a-5p is a potential prognostic marker of delayed lymph node metastasis in early-stage tongue squamous cell carcinoma

Abstract: MicroRNAs (miRs) are expected to serve as prognostic tools for cancer. However, many miRs have been reported as prognostic markers of recurrence or metastasis in oral squamous cell carcinoma patients. We aimed to determine the prognostic markers in early-stage tongue squamous cell carcinoma (TSCC). Based on previous studies, we hypothesized that miR-10a, 10b, 196a-5p, 196a-3p, and 196b were prognostic markers and we retrospectively performed miR expression analyses using formalin-fixed paraffin-embedded sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 126 publications
(214 reference statements)
0
22
0
Order By: Relevance
“…qPCR amplification parameters were: Annealing at 25˚C for 10 min, extension at 42˚C for 30 min; inactivation at 85˚C for 10 min, after extension of the detection of fluorescence signals, a total of 40 cycles. The 2 -ΔΔCq method ( 16 ) was used to quantify the relative mRNA expression of the target and housekeeping genes. The following primers were used: XIST forward, 5'-ACGCTGCATGTGTCCTTAG-3 and reverse, 5'-GAGCCTCTTATAAGCTGTTTG-3'; miR-155-5p forward, 5'-GAGGGTTAATGCTAATCGTGATAGG-3' and reverse, 5'-GCACAGAATCAACACGACTCACTAT-3'; GAPDH forward, 5'-CTGGGCTACACTGAGCACC-3' and reverse, 5'-AAGTGGTCGTTGAGGGCAATG-3'; and U6 forward, 5'-GAGGGTTAATGCTAATCGTGATAGG-3' and reverse, 5'-GCACAGAATCAACACGACTCACTAT-3'.…”
Section: Methodsmentioning
confidence: 99%
“…qPCR amplification parameters were: Annealing at 25˚C for 10 min, extension at 42˚C for 30 min; inactivation at 85˚C for 10 min, after extension of the detection of fluorescence signals, a total of 40 cycles. The 2 -ΔΔCq method ( 16 ) was used to quantify the relative mRNA expression of the target and housekeeping genes. The following primers were used: XIST forward, 5'-ACGCTGCATGTGTCCTTAG-3 and reverse, 5'-GAGCCTCTTATAAGCTGTTTG-3'; miR-155-5p forward, 5'-GAGGGTTAATGCTAATCGTGATAGG-3' and reverse, 5'-GCACAGAATCAACACGACTCACTAT-3'; GAPDH forward, 5'-CTGGGCTACACTGAGCACC-3' and reverse, 5'-AAGTGGTCGTTGAGGGCAATG-3'; and U6 forward, 5'-GAGGGTTAATGCTAATCGTGATAGG-3' and reverse, 5'-GCACAGAATCAACACGACTCACTAT-3'.…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs (miRNAs), small non-coding RNAs, play considerable roles in the development of cancer. For instance, miR-196a-5p is a potential prognostic marker of delayed lymph node metastasis in early stage TSCC (Maruyama et al, 2018). It is found that miR-488 is significantly decreased in TSCC tissues and cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…In present review, miRNAs showing statistical significant ( P ≤ .01) correlation with lymph node metastasis includes miRNA 34a, miRNA 196‐5p, miRNA 196‐3p, miRNA 519d, and miRNA 21. All these miRNAs are expressed in tongue squamous cell carcinoma 25‐28 . Also one more common aspect we noticed here is all these miRNAs targets the biomarkers (mRNAs) controlling the epithelial to mesenchymal cell transition (EMT).…”
Section: Discussionmentioning
confidence: 62%